Clinical Diagnosis of Scapular Dyskinesis in a Youth Softball Pitcher: A Case Report - Connor Skoumal; Matt Dewald (North American Sports Medicine Institute, 2024)
# Introduction Effective rehabilitation strategies for upper extremity injuries in softball pitchers are scarce in current literature, especially among youth athletes. Additionally, there continues to be ambiguity regarding the interpretation and clinical practicality when treating an overhead athlete with scapular dyskinesis. The purpose of this case report is to highlight the examination and treatment of a youth softball pitcher referred to physical therapy with the diagnosis of scapular dyskinesis. # Case Description This case report presents data and outcomes for a 14-year-old female who experienced chronic right shoulder discomfort related to performing the windmill softball pitch (WSP). The subject was clinically diagnosed with scapular dyskinesis by her referring physician and demonstrated abnormal scapular movement when elevating and lowering her upper extremity. Internal and external rotator isokinetic strength testing and the Athletic Shoulder Test (ASH) were used as primary objective measures. Both were performed six days after the initial evaluation and again six weeks later. Initial testing demonstrated decreased peak torque and total work. Initial treatment involved periscapular and shoulder strengthening with progression to overhead loading. Later rehabilitation strategies focused on neuromuscular control, functional training, and sport-specific activities. # Outcomes The subject initially demonstrated improved peak torque and total work of the shoulder with isokinetic strength testing but continued to have symptoms with pitching, even though the Scapular Dyskinesis Test had become negative. After changing the focus to neuromuscular and functional training the subject had fewer symptoms and became comfortable with self-management. # Discussion This case matches previous research that endorses scapular dyskinesis being a normal finding in overhead athletes with and without shoulder pain. Neuromuscular control and functional training after a period of scapular strengthening were beneficial in improving symptoms in this athlete. # Level of Evidence 5